Managers and Students as Newsvendors - Bolton, Gary E.; Ockenfels, Axel; Thonemann, Ulrich W. (Management Science, 2012)
We compare how experienced procurement managers and students solve the newsvendor problem. We find that managers broadly exhibit the same kind of pull-to-center bias as students do. Also, managers use information and task training no better than students. The performance of managers is positively affected by the level of their education and their level in the organizational hierarchy. We discuss implications for theory and for how ordering might be improved in practice. This paper was accepted by Teck Ho, decision analysis.